SHOBAHUL LUGHOH'S EFFECTIVENESS IN IMPROVING ENGLISH SPEAKING SKILLS OF MAHASANTRI AT MA'HAD AL-JAMI'AH SAYYID ALI RAHMATULLAH - Thoyyibah, Elok Abidatut (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
English speaking skills are an essential component in mastering a foreign language, especially for students in the context of Islamic education. This study analyzes the effectiveness and impact of Shobahul Lughoh learning on improving students' speaking skills at Ma’had Al-Jami’ah UIN Sayyid Ali Rahmatullah Tulungagung. Using a mixed methods approach with a quasi-experimental nonequivalent control group design and semi-structured interviews, the sample consisted of 76 students (40 in the experimental group and 36 in the control group). Data were collected through speaking tests (pre-test and post-test) and interviews with eight participants from the experimental group. Quantitative analysis using t-tests showed a significant difference between the experimental and control groups (t(74)=4.82, p=0.000 < 0.05). The average speaking ability score of the experimental group increased from 45.12 to 61.87, while the control group only increased from 44.88 to 48.25. Qualitatively, the interview findings revealed an increase in self-confidence, fluency in spontaneous speaking, and vocabulary enrichment in daily communication. The Shobahul Lughoh program has been empirically and pedagogically proven effective in improving speaking competence, with implications for integrating Islamic values such as discipline and collaboration in language learning. This study provides new contributions to the study of practice-based language learning in Islamic educational settings, as well as recommendations for the development of similar programs. ABSTRAK Keterampilan berbicara bahasa Inggris merupakan komponen esensial dalam penguasaan bahasa asing, terutama bagi mahasantri di konteks pendidikan Islam. Penelitian ini menganalisis efektivitas dan dampak pembelajaran Shobahul Lughoh terhadap peningkatan keterampilan berbicara mahasantri di Ma’had Al-Jami’ah UIN Sayyid Ali Rahmatullah Tulungagung. Menggunakan pendekatan mixed methods dengan desain quasi-experimental nonequivalent control group dan wawancara semi-terstruktur, sampel terdiri dari 76 mahasantri (40 kelompok eksperimen dan 36 kelompok kontrol). Data dikumpul melalui tes berbicara (pre-test dan post-test) serta wawancara dengan delapan partisipan dari kelompok eksperimen. Analisis kuantitatif menggunakan t-test menunjukkan perbedaan signifikan antara kelompok eksperimen dan kontrol (t(74)=4.82, p=0.000 < 0.05). Rata-rata skor kemampuan berbicara kelompok eksperimen meningkat dari 45,12 menjadi 61,87, sedangkan kelompok kontrol hanya meningkat dari 44,88 menjadi 48,25. Secara kualitatif, temuan wawancara mengungkap peningkatan kepercayaan diri, kelancaran berbicara spontan, serta pengayaan kosakata dalam komunikasi sehari-hari. Program Shobahul Lughoh terbukti efektif secara empiris dan pedagogis dalam meningkatkan kompetensi berbicara, dengan implikasi integrasi nilai-nilai Islam seperti disiplin dan kolaborasi dalam pembelajaran bahasa. Penelitian ini memberikan kontribusi baru pada kajian pembelajaran bahasa berbasis praktik di lingkungan pendidikan Islam, serta rekomendasi untuk pengembangan program serupa.